A Rare Case of Necrotizing Fasciitis as Side Effect of Methimazole Administration for Basedow Disease - Tito Brambullo; Alberto De Lazzari; Gian Paolo Azzena; Giuseppe Masciopinto; Vincenzo Vindigni (International Journal of Innovative Research in Medical Science, 2021)
A rare case of agranulocytosis due to Methimazole administration for Basedow disease is presented. After 30 days since the therapy beginning a 45 year old female patient has developed a necrotizing fasciitis on both legs, with muscle bellies and Achille’s tendon exposure. Immediate surgical debridement was necessary to save her life and control the progression of infection. Several plastic surgery procedures were performed to accomplish wounds healing (vacuum-assisted closure therapy, dermal substitute, free flap, skin graft), and after 75 days the patient was discharged. An intensive rehabilitation program permitted a complete functional recovery. After 12 months a reshaping procedure was performed to improve right leg and ankle contour. The close cooperation between endocrinologist and surgeon revealed to be essential to perform a safe surgery and to permit the return to the job and daily activities.